Validation of the DNATyper™15 PCR Genotyping System for Forensic Application - Jian Ye; Chengtao Jiang; Xingchun Zhao; Le Wang; Caixia Li; Anquan Ji; Li Yuan; Jing Sun; Shuaifeng Chen (Wolters Kluwer Medknow Publications, 2015)
We describe the optimization and validation of the DNATyper™15 multiplex polymerase chain reaction (PCR) genotyping system for autosomal short tandem repeat (STR) amplification at 14 autosomal loci (D6S1043, D21S11, D7S820, CSF1PO, D2S1338, D3S1358, D13S317, D8S1179, D16S539, Penta E, D5S818, vWA, D18S51, and FGA) and  amelogenin, a sex-determining locus. Several DNATyper™15 assay variables were optimized, including hot start Taq polymerase concentration, Taq polymerase activation time, magnesium concentration, primer concentration, annealing temperature, reaction volume, and cycle number. The performance of the assay was validated with respect to species specificity, sensitivity to template concentration, stability, accuracy, influence of the DNA extraction methods, and the ability to genotype the mixture samples. The performance of the DNATyper™15 system on casework samples was compared with that of two widely used STR amplification kits, Identifiler™ (Applied Biosystems, Carlsbad, CA, USA) and PowerPlex 16 ® (Promega, Madison, WI, USA). The conditions for PCR-based DNATyper™15 genotyping were optimized. Contamination from forensically relevant nonhuman DNA was not found to impact genotyping results, and full profiles were generated for all the reactions containing ≥ 0.125 ng of DNA template. No significant difference in performance was observed even after the DNATyper™15 assay components were subjected to 20 freeze-thaw cycles. The performances of DNATyper™15, Identifiler™, and PowerPlex 16 ® were comparable in terms of sensitivity and the ability to genotype the mixed samples and case-type samples, with the assays giving the same genotyping results for all the shared loci. The DNA extraction methods did not affect the performance of any of the systems. Our results demonstrate that the DNATyper™15 system is suitable for genotyping in both forensic DNA database work and case-type samples.